Astragalus polysaccharides protect cardiac stem and progenitor cells by the inhibition of oxidative stress-mediated apoptosis in diabetic hearts - Chen W; Ju J; Yang Y; Wang H; Chen W; Zhao X; Ye H; Zhang Y (Drug Design, Development and Therapy, 2018)
Wei Chen,1 Jing Ju,1 Yehong Yang,2 Hao Wang,3 Wenjie Chen,1 Xuelan Zhao,1 Hongying Ye,2 Yu Zhang1 1Department of Geriatrics, Huashan Hospital, Fudan University, Shanghai, China; 2Department of Endocrinology, Huashan Hospital, Fudan University, Shanghai, China; 3Core Center of Animal Facility, School of Medicine, Fudan University, Shanghai, China Introduction: Diabetic cardiomyopathy is characterized by an imbalance between myocyte death and regeneration mediated by the progressive loss of cardiac stem and progenitor cells (CSPCs) by apoptosis and necrosis due to the activation of oxidative stress with diabetes. In this study, we evaluated the beneficial effect of astragalus polysaccharides (APS) therapy on the protection of CSPCs through its antioxidative capacity in diabetic hearts.Materials and methods: Streptozotocin (STZ)-induced diabetic mice and heterozygous (SOD2+/-) knockout mice were employed and administered with APS. Ventricular CSPCs were isolated for oxidative evaluation. The abundance, apoptosis and proliferation, reactive oxygen species (ROS) formation, oxidative damage, and SOD2 protein levels and activities were evaluated in ventricular CSPCs.Results: We confirmed that APS increased the CSPC abundance, reduced the apoptosis of CSPCs, and enhanced the proliferation of CSPCs in both STZ-induced diabetic mice and nondiabetic SOD2+/- mice. In addition, therapy of APS enhanced SOD2 protein levels and enzyme activities, and inhibited ROS formation and oxidative damage of CSPCs from both STZ-induced diabetic mice and nondiabetic SOD2+/- mice.Conclusion: Our findings demonstrated the positive effect of APS on the rescue of CSPC preservation in diabetes, dependent on the inhibition of oxidative stress-mediated apoptosis. Keywords: diabetes, cardiac stem cells, cardiac progenitor cells, oxidative stress, cardiomyopathy, oxidation